BOOK REVIEWS (Journal of Finance, 1982)
Book reviewed in this article: A History of Retirement . By WILLIAM GRAEBNER. Investing in Securities: An Efficient Markets Approach . By SEHA M. TINIC and RICHARD R. WEST. Investment Analysis and Management . By ANTHONY J. CURLEY and ROBERT M. BEAR. Investment Analysis and Portfolio Management . By SID MITTRA and CHRIS GASSEN. Analytical Techniques for Financial Management . By JEROME S. OSTERYOUNG and DANIEL E. McCARTY. Financial Management: Theory and Strategies . By EDWIN H. NEAVE and JOHN C. WIGINTON. Managerial Finance: Theory and Techniques . By DENNIS J. O'CONNOR and ALBERTO T. BUESO.